The Predictive Value of Early Changes in 18F‐Fluoroestradiol Positron Emission Tomography/Computed Tomography During Fulvestrant 500 mg Therapy in Patients with Estrogen Receptor‐Positive Metastatic Breast Cancer. (28th April 2020) - He, Min; Liu, Cheng; Shi, Qin; Sun, Yuyun; Zhang, Yongping; Xu, Xiaoping; Yuan, Huiyu; Zhang, Yingjian; Liu, Yin; Liu, Guangyu; Di, Genhong; Yang, Zhongyi; et al.
Abstract: Background: The aim of this study was to investigate the predictive value of early changes in 18 F‐fluoroestradiol (FES) positron emission tomography (PET)/computed tomography (CT) during fulvestrant 500 mg therapy in patients with estrogen receptor (ER)‐positive metastatic breast cancer. Materials and Methods: Patients underwent 18 F‐FES PET/CT scans at both baseline (scan 1) and day 28 (scan 2). The maximum standardized uptake value (SUVmax) of all metastatic sites was determined in each scan, and the percentage reduction in SUVmax (ΔSUVmax) was calculated as [(SUVmax on scan 1‐SUVmax on scan 2)/ SUVmax on scan 1] * 100%. Results: In total, 294 18 F‐FES‐positive lesions from 36 patients were identified. The 18 F‐FES SUVmax varied widely among lesions (median 5.7; range 1.8–32.4) and patients (median 5.1; range 2.5–13.2). After treatment, the median SUVmax among lesions and patients was 2.1 and 2.1, respectively. The ΔSUVmax ranged from −5.1% to 100%, with a median reduction of 61.3%. Using receiver operating characteristic analysis, the optimal cutoff point to discriminate patients who could derive clinical benefit from fulvestrant was determined to be 38.0%. Patients with a median ΔSUVmax ≥38.0% experienced significantly longer progression‐free survival (PFS) than those with ΔSUVmax <38.0% (28.0 months vs. 3.5 months, p = .003). Multivariate analysis demonstrated that ΔSUVmax ≥38.0% was an independent predictor of PFS benefit in patients receiving fulvestrant therapy. Conclusion: Changes in SUVmax measured by serial imaging of 18 F‐FES PET/CT could be used early to predict PFS benefit in patients receiving fulvestrant therapy. Implications for Practice: The aim of this study was to evaluate the role of 18 F‐fluoroestradiol (FES) positron emission tomography (PET)/computed tomography (CT) in predicting response to fulvestrant 500 mg therapy in patients with hormone receptor‐positive/human epidermal growth receptor 2–negative metastatic breast cancer. This study highlights the utility of FES PET/CT as a predictive factor to discriminate patients who might benefit from fulvestrant. Moreover, these findings showed that this molecular imaging technique might be a potential tool for physicians to make individualized treatment strategies. Abstract : This study investigated whether changes in 18 F‐FES positron emission tomography uptake could be used for the early prediction of treatment response in patients with metastatic breast cancer who received a fulvestrant 500 mg regimen.